Mesoscale aggregation properties of C60 in toluene and chlorobenzene. Issue 29 (4th July 2016) - Guo, Rong-Hao; Hua, Chi-Chung; Lin, Po-Chang; Wang, Ting-Yu; Chen, Show-An
Abstract : Solvent-induced, nanoscale aggregate units lead to a hierarchy of mesoscale aggregation features as revealed by multiscale experimental schemes. Abstract : The mesoscale aggregation properties of C60 in two distinct aromatic solvents (toluene and chlorobenzene) and a practical range of concentrations ( c = 1–2 and c = 1–5 mg mL −1, respectively) were systematically explored by static/dynamic light scattering (SLS/DLS), small angle X-ray scattering (SAXS), depolarized dynamic light scattering (DDLS), and cryogenic transmission electron microscopy (cryo-TEM) analyses. The central observations were as follows: (1) aggregate species of sizes in the range of several hundred nanometers have been independently revealed by SLS, DLS, and DDLS analyses for both solvent systems. (2) DDLS and cryo-TEM measurements further revealed that while C60 clusters are notably anisotropic (rod-like) in chlorobenzene, they are basically isotropic (spherical) in toluene. (3) Detailed analyses of combined SLS and SAXS profiles suggested that varied, yet self-similar, solvent-induced aggregate units were responsible for the distinct (mesoscale) aggregation features noted above. (4) From a dynamic perspective, specially commissioned DLS measurements ubiquitously displayed two relaxation modes (fast and slow mode), with the second (slow) mode being q (wave vector) independent. While the fast mode in both solvent systems was basically diffusive by nature and leads to geometrical features in good agreement with the above static analyses, the slow mode was analyzed and tentatively suggested to reflect the effect of mutual confinement. (5) Micron-scale aggregate morphology of drop-cast thin films displays similar contrasting features for the two solvent media used. Overall, this study suggests that solvent-induced, nanoscale, aggregate units may be a promising factor to control a hierarchy of microscopic aggregation properties of C60 solutions and thin films.